Efektivitas Campuran Ekstrak Daun Srikaya (Annona squamosal L.) dan Rimpang Kunyit (Curcuma domestica Val.) pada Mortalitas Larva Spodoptera litura F. (Lepidoptera: Noctuidae) - Ramadhan Taufika; Setyo Andi Nugroho; Anni Nuraisyah (Jurnal Ilmu Pertanian Indonesia, 2021)
Spodoptera litura F. larvae (Lepidoptera: Noctuidae) are polyphagous insects that cause damages to many types of plantations and horticulture that need to be protected. One of environmentally friendly method to protect ecological balance is the use of botanical insecticides whose bioactive compounds come from plant extracts. This study used a mixture of two plant extracts from A. squamosa leaves extract and C. domestica rhizome exstract (the mixed of experimental extracts). The mixed of experimental extracts are synergistic so that they are more effective and need a lower concentration to cause the mortality of S. litura larvae than the use of a single extract. The aims of the research were to know the efficacy of the mixed of experimental extracts on the mortality of S. litura larvae and determine the value of LC50 and LC90 extract test on its mortality. The initial and efficacy test were conducted by bait dip into the mixed of experimental extracts. The mortality data were analyzed using ANAVA, then continued by Duncan test and Probit analysis. The results of this research showed that the mixed of experimental extracts were effective to kill S. litura larvae. The calculated result of LC50 and LC90 showed that the LC50 value of the experimental extracts on the second and the third instar larvae were 5.252 ppm and 10.559 ppm, respectively, and the LC90 value for both instar larvae were 11.124 ppm and 13.638 ppm, respectively. It could be concluded that the mixed of experimental extracts is effective in S. litura larvae mortality and more effective in the mortality of the second instar larvae than that of the third instar larvae. Therefore, this test extract mixture can be developed further in a greenhouse to evaluate the effectiveness in the mortality of S. litura larvae which can be used as an alternative to controlling S. litura larvae with an environmentally friendly material in farmers. Keywords: control, extract, mortality, Spodoptera litura